Pembinaan dan Pedampingan Kader Santri Sehat Dalam Mewujudkan Pola Hidup Bersih dan Sehat (PHBS) di Ponpes Al-Mubarok - Nurmeily Rachmawati; Venny Patricia; Syarah Anliza (Jurnal Pengabdian Masyarakat - PIMAS, 2026)
One of the government's health development programs, outlined in the National Medium-Term Development Plan (RPJMN), relates to the national development strategy and programs of each ministry over a specific timeframe, namely towards a Indonesia Sehat, namely Clean and Healthy Living Behavior (PHBS). However, this program continues to be implemented because not all provinces have significantly improved PHBS. One indicator of the PHBS program is preventing the spread of infectious diseases through handwashing with antiseptic and using clean water. The goal of this community service activity to address partner issues is to increase the students' knowledge of PHBS, particularly regarding handwashing with soap, proper handwashing, and soap-making skills. The results showed that the knowledge of students increase by results of pre and posttest. The number of germs before and after washing hands were decreased. The students implemented PHBS very well by making soap from kit soap that been given.